La planificación tributaria en el sector turístico y hotelero y su incidencia en la rentabilidad de la provincia de Tungurahua en el periodo 2015-2020 - Flores Taipe, Tania Yadira (2023)
The present investigation was carried out with the purpose of establishing the incidence of tax planning on the profitability of companies that, due to their activity, belong to the tourism and hotel sector of the province of Tungurahua. In this regard, incentives are a fiscal tool that allows the local, regional and national development of a state, which contribute to the generation of employment, attraction of investments among other development alternatives, however, these must be planned before starting a new fiscal period. Once the statistical and documentary information has been obtained, it has been possible to demonstrate the weaknesses of the sector.